PEMBUATAN SISTEM INFORMASI LAYANAN UMUM BERBASIS ANDROID OS SEBAGAI BUKU PANDUAN DIGITAL DI YOGYAKARTA - , ANDANG RIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are numerous public services in Yogyakarta. People really need the information of public services in this city. For example is a provider service of taxi. Most people do not save the contact number of the taxi. So, they have to seek and wait to find a taxi that they want. Jogja Smartbook Application is an Android based mobile application that fill the contact numbers of public service providers in Yogyakarta, such as hotel providers, taxi, motor taxi, villa, home stay, guesthouse, etc. This application can be made easier for people to find the services they want. There is a contact number and also some additional menu tab such as menu facility, menu gallery, menu info, and menu price. So, it is very easy to operate by the user.